Mombaça grass yield as a function of nitrogen fertilization based on the use of the chlorophyll meter - Ferreira Leite, Lorrayne Lays; Backes, Clarice; de Godoy, Leandro José Grava [UNESP]; Marques Santos, Alessandro José; Teodoro, Arthur Gabriel; Rodrigues, Lucas Matheus; de Resende, Cinthya Cristina Fernandes; Ribon, Adriana Aparecida (Universidade Estadual de Londrina, 2021)
The objective of this study was to evaluate the yield and agronomic efficiency of mombaça grass achieved with the management of nitrogen fertilization, based on the nitrogen sufficiency index (NSI) calculated using measurements obtained with a chlorophyll meter. The experiment was conducted in the field, in São Luís de Montes Belos - GO, Brazil, from November 2016 to May 2018, as a randomized-block design with six treatments and five replicates. Treatments consisted of six N fertilization management strategies (M), namely, M1 - reference, with 150 kg ha-1 N per application; M2 - recommended, with 50 kg ha-1 N per application; M3 - 50 kg ha-1 N when NSI < 98%; M4 - 50 kg ha-1 N when NSI < 94%; M5 - 50 kg ha-1 N when NSI < 90%; and M6 - control treatment, without N application. The NSI was monitored based on the relative chlorophyll content obtained with the chlorophyll meter. Forage canopy height, tiller density, and yield were evaluated. At the end of the 2nd cycle, the recommended, reference, NSI98%, NSI94%, and NSI90% treatments had received 1,050, 350, 300, 250, and 0 kg N ha-1. Control treatment obtained the lowest dry biomass yield, whereas the recommended, NSI98%, and NSI94% treatments showed the highest. Thus, N doses between 1,950 and 300 kg ha-1, in the second cycle, provided statistically equivalent yields in mombaça grass. Considering the DM of both evaluation cycles, the highest yield was achieved with the NSI98% and NSI94% treatments. The application of N doses of 250 to 1050 kg ha-1 provided similar yields. Therefore, the adoption of a nitrogen sufficiency index below 98% and 94% as a parameter allows a reduction and rational use of nitrogen fertilizer.
Produtividade do capim mombaça em função da adubação nitrogenada baseada no uso do clorofilômetro
Keywords: Antifungal effect; Essential oil; Spices